DIRECTIONS FOR INCREASING ENERGY RESOURCE EFFICIENCY THROUGH THE TRANSITION TO A “GREEN” ECONOMY - Masharipova S. R. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: Nowadays, issues of ecological sustainability and rational use of resources are coming to the agenda on a global scale. In particular, the need to transition to the principles of the “green” economy in industrial sectors is steadily increasing. Excessive consumption of energy resources, environmental pollution, and the increase in carbon dioxide emissions are creating serious problems for humanity. Therefore, the introduction of energy-saving technologies, the wide use of renewable energy sources, and the increase of energy efficiency in industry have become one of the global priority directions.